2017
DOI: 10.1111/imj.13231
|View full text |Cite
|
Sign up to set email alerts
|

Trends and outcomes of chronic kidney disease in intensive care: a 5‐year study

Abstract: CKD prevalence amongst patients admitted to hospital and ICU is increasing and is associated with worse outcomes. ElixRF may be a useful administrative flag for nephrologist involvement in care and for prompting consideration of advanced care planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…With the slow progression of CKD accompanied by acute and unpredictable exacerbations of clinical problems (Ngu et al . ), concomitant comorbid conditions and multiplicity of treatment pathways (conservative, renal replacement therapies), flexible and extended palliative care support may be required. The current models of PCS which tend to focus on the later stages of decline may not be a good fit for the varied population with CKD.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With the slow progression of CKD accompanied by acute and unpredictable exacerbations of clinical problems (Ngu et al . ), concomitant comorbid conditions and multiplicity of treatment pathways (conservative, renal replacement therapies), flexible and extended palliative care support may be required. The current models of PCS which tend to focus on the later stages of decline may not be a good fit for the varied population with CKD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a large retrospective Australian study of people who had accessed PCS (n ¼ 12,817), those with renal failure (8.9% of the sample; CKD stage and modality type were not reported) received a median of six days of PCS as compared with 30 days received by those with a cancer diagnosis (56% of the total sample) (Rosenwax et al 2016). With the slow progression of CKD accompanied by acute and unpredictable exacerbations of clinical problems (Ngu et al 2017), concomitant comorbid conditions and multiplicity of treatment pathways (conservative, renal replacement therapies), flexible and extended palliative care support may be required. The current models of PCS which tend to focus on the later stages of decline may not be a good fit for the varied population with CKD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…high-risk patients can account for a large proportion of healthcare resources [17]. Critical illness is associated with greater length of stay, in-hospital mortality, and risk of dialysis dependence in observational studies among patients with CKD [3,4,18]. Our findings add to a growing field of data on CKD-related hospitalization and extend this to those in low socioeconomic settings for whom limited information is available.…”
Section: Discussionmentioning
confidence: 53%
“…Chronic kidney disease (CKD) is an independent risk factor for hospitalization, and this risk increases with a decline in estimated glomerular filtration rate (eGFR) [1,2]. The utilization of inpatient critical care services is associated with higher costs and poorer outcomes in patients with CKD [3]. Kidney disease, even at early stages, increases the risk for critical illness due to alterations in acid-base homeostasis, electrolyte imbalances, volume dysregulation, immunosuppression, and anemia.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia CKD is associated with 17% of all hospitalisations [ 5 ]. Ngu et al found that inpatient admissions (IPA) due to CKD in Australia significantly increased over a four-year period from 5.2% to 8.6% of all hospital admissions, and of intensive care admissions from 8.3% to 13.3% [ 11 ]. CKD is often related to, or is an underlying condition in, many other admitted disease groups, such as cardiovascular and diabetes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%